Variation in qualitative and quantitative traits of cassava germplasm from selected national breeding programmes in subSaharan Africa - Kawuki, Robert S.; Ferguson, Morag E.; Labuschagne, Maryke T.; Herselman, L.; Orone, J.; Ralimanana, I.; Bidiaka, M.; Lukombo, S.; Kanyange, M.C.; Gashaka, G.; Mkamilo, G.S.; Gethi, J. (Elsevier, 2011)
An improved understanding of phenotypic variation within cassava germplasm in southern, eastern and central Africa will help to formulate knowledge-based breeding strategies. Thus, the overall objective of this study was to examine the phenotypic variation in cassava germplasm available within six breeding programmes in Africa, namely Uganda, Kenya, Tanzania, Rwanda, Democratic Republic of Congo and Madagascar. In each country, single-row plots were used for assessment of 29 qualitative traits and evaluation of four quantitative traits: root dry matter content (DMC), harvest index (HI), leaf retention (LR) and root cortex thickness. Qualitative traits provided limited discrimination of cassava germplasm. However, differences in DMC, HI, LR and root cortex thickness were observed among the germplasm indicating scope for genetic improvement. Highest average DMC was registered in Uganda (39.3%) and lowest in Tanzania (30.1%), with the elite genotypes having a relatively higher DMC than local genotypes. Highest average HI was observed in Uganda (0.60) and lowest in Kenya (0.32). Cassava genotypes displayed varied root peel thickness (0.34–4.89 mm). This study highlights variation in agronomic traits that could be exploited to increase cassava productivity.